Towards Sustainable Offshore Outsourcing: A Case Study of Quebec Manufacturing Firms Outsourcing to China - Mohiuddin, Muhammad; Su, Zhan; Su, Albert (Pontificia Universidad Católica del Perú. CENTRUM, 2010)
The offshore-outsourcing choice is viewed as a source of factory closures and job losses in many developed countries including Canada. The current exploratory paper using qualitative case study methods presents experiences from four Canadian companies based in the province of Quebec. It shows that offshore outsourcing is an important business strategy that can create overall firm-level competitiveness through the generation of more revenues, higher profits, better customer satisfaction, and increased investments in R&D and core competency development.
Keywords: China; Competitiveness; Core Competence; New Global Division of Labor (NGDL).; Sustainable Offshore-Outsourcing; https://purl.org/pe-repo/ocde/ford#5.02.04